Towards a New Strategic Partnership between Asia and Africa - Ali Alatas (2016)
ALMOST exactly 50 years ago, in April 1955, in the Indonesian city of Bandung, the leaders of 29 Asian and African nations, comprising those newly independent and those still struggling to break free from colonialism, convened the Asian-African Conference.